Overview of institutional gender audit report - Abebe, Lemlem (Ethiopian Institute of Agricultural Research, 2018)
Presented by Lemlem Abebe (EIAR), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.